1954
DOI: 10.4039/ent8665-2
|View full text |Cite
|
Sign up to set email alerts
|

Avian Mallophaga from Quebec

Abstract: Following the lead set by Dr. George M. Stirrett, (Canadian Entomologist, July, 1952), the following records of Mallophaga from avian hosts taken in the province of Quebec have been assembled. It is hoped that others will record collections made in their respective provinces, so that eventually records and the distribution of species may be available for the Dominion.The following species were largely collected by the author, with some assistance from the late Dr. W. E, Swales. The specimens form part of the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1971
1971
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Considering the diversity and abundance of woodpeckers in Canada and the relative stability in taxonomy of their lice, surprisingly little attention has been paid to their relationships, other than for the species of lice appearing in various lists of ectoparasites published more than 50 years ago ( e . g ., Thompson 1934; Whitehead 1934; Brown and Wilk 1944; Spencer 1948; Stirrett 1952; Judd 1953). The only recently published records of lice on woodpeckers in Canada are those of Threlfall and Wheeler (1986), and that almost 30 years ago, and Galloway et al .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the diversity and abundance of woodpeckers in Canada and the relative stability in taxonomy of their lice, surprisingly little attention has been paid to their relationships, other than for the species of lice appearing in various lists of ectoparasites published more than 50 years ago ( e . g ., Thompson 1934; Whitehead 1934; Brown and Wilk 1944; Spencer 1948; Stirrett 1952; Judd 1953). The only recently published records of lice on woodpeckers in Canada are those of Threlfall and Wheeler (1986), and that almost 30 years ago, and Galloway et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although Price et al (2003) reported 12 species of chewing lice on the ubiquitous rock pigeon, only three species have been reported in Canada: Bonomiella columbae Emerson (Menoponidae) from British Columbia (Emerson 1957b), Campanulotes compar (Burmeister) (Philopteridae) from Alberta (Brown and Wilk 1944) and Quebec (Raynor 1932;Whitehead 1934Whitehead , 1954, and Columbicola columbae (L.) (Philopteridae) from British Columbia (Spencer 1928(Spencer , 1948(Spencer , 1957, Alberta (Brown and Wilk 1944), Ontario (Stirrett 1952), and Quebec (Raynor 1932;Thompson 1934;Whitehead 1934Whitehead , 1954. The rock pigeon is very common in southern Canada and there are many unpublished records for these lice in various collections; however, no one has gathered the information together.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies where lice were collected locally in general surveys (e.g., Twinn 1935, Judd 1953, Teskey 1960, Thompson 1968) or from specific hosts (e.g., Buscher 1965, Judd 1968, Ballard and Ring 1979, Dick 1981, Colwell et al 2008, Yunik et al 2016). In regional initiatives, Spencer (1928, 1939, 1948, 1957) collected intensively in British Columbia, and species lists of chewing lice were compiled for Quebec by Rayner (1932) and Whitehead (1934, 1954) and for Alberta by Brown and Wilk (1944). William Threlfall and his students recorded lice from a number of hosts in Newfoundland (e.g., Andrews and Threlfall 1975, Bourgeois and Threlfall 1981, Eveleigh and Threlfall 1974, Fitzpatrick and Threlfall 1977, Threlfall et al 1979, Threlfall and Wheeler 1986, Wheeler and Threlfall 1986).…”
mentioning
confidence: 99%